Iowa Birdline update, November 6 & 8, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Notes for the Iowa Birdline update for November 6, 1993. Highlights include sightings of a White-winged Scoter, Snowy Owl, Long-tailed Duck, and Surf Scoter. Includes notes for the Iowa Birdline update for November 8, 1993. Epson - sheet feed/flatbed